1995
DOI: 10.1164/ajrccm.152.3.7663779
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of tracheal colonization during mechanical ventilation.

Abstract: The relationship between gastric (GC) and tracheal (TC) colonization and the development of ventilator-associated pneumonia (VAP) remains controversial. TC, GC, and pharyngeal (PC) colonization were studied serially in 80 patients with mechanical ventilation (MV) to ascertain the routes and onset of TC. Simultaneous sample from pharynx, stomach, and trachea were obtained throughout the MV period. Quantitative cultures were performed. Seventy-two patients (90%) had TC at some time during MV. Only 19 patients pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
1
4

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(45 citation statements)
references
References 0 publications
3
37
1
4
Order By: Relevance
“…Because of the specific aims of our study and therefore its design, comparison with existing data is difficult. However, our results expand those previously published dealing with GNB colonization, indicating increasing levels of colonization with increasing patient severity and subsequent risk for VAP [37][38][39].…”
Section: Discussionsupporting
confidence: 90%
“…Because of the specific aims of our study and therefore its design, comparison with existing data is difficult. However, our results expand those previously published dealing with GNB colonization, indicating increasing levels of colonization with increasing patient severity and subsequent risk for VAP [37][38][39].…”
Section: Discussionsupporting
confidence: 90%
“…The following data were recorded in each case: age and sex of the patient, reasons for mechanical ventilation, type of humidification used (humidifier in the ventilator circuit or heat and moisture exchanger), duration of ventilation, means of respiratory access (oral or nasal ETT or tracheostomy), method of stress ulcer prophylaxis (histamine type 2-receptor blockers or barrier preparation, i.e. sucralfate), the occurrence or not of nosocomial pneumonia, together with data of suspected nosocomial pathogens, using criteria similar to those previously described [10,11].…”
Section: Patient Datamentioning
confidence: 99%
“…L -1 ; 4) purulent tracheobronchial secretions; and 5) no evidence of infection elsewhere. Organisms cultured in significant amounts (2+ (20±100 colonies) and 3+ (>100 colonies) growth) from good quality specimens of secretions obtained by sterile suctioning of the lower respiratory tract through the ETT or tracheostomy tube were considered to be likely causative pathogens, as previously described [10].…”
Section: Patient Datamentioning
confidence: 99%
“…In a study by de Latorre et al [13]64 of 80 patients (80%) showed colonization of the trachea within the first 24 h of mechanical ventilation. In a selected cohort of patients with severe exacerbation of chronic obstructive pulmonary disease, bacterial colonization of 72% during the 1st day of mechanical ventilation was reported [14].…”
Section: Introductionmentioning
confidence: 99%